2012
DOI: 10.1177/1941874412450716
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Leading US Neurology Departments

Abstract: Objective: To determine the current practice and plans for telemedicine at leading US neurology departments. Design and Setting: An electronic survey was sent to department chairs, administrators, or faculty involved in telemedicine at 47 neurology departments representing the top 50 hospitals as ranked by U.S. News and World Report. Main Outcome Measures: Current use, size, scope, reimbursement, and perceived quality of telemedicine services. Results: A total of 32 individuals from 30 departments responded (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 18 publications
0
49
0
Order By: Relevance
“…A 2012 survey of leading U.S. neurology departments, for example, found that over 85% have or planned to implement telemedicine programs within the next year and that, next to stroke, movement disorders was the most common application. 48 As detailed by members of the International Parkinson and Movement Disorder Society (MDS) Task Force on Telemedicine in the Appendix, telemedicine programs for PD of various stages of maturity are operating globally and focus on both care and educational activities.…”
Section: Present: Increasing Access To Carementioning
confidence: 99%
“…A 2012 survey of leading U.S. neurology departments, for example, found that over 85% have or planned to implement telemedicine programs within the next year and that, next to stroke, movement disorders was the most common application. 48 As detailed by members of the International Parkinson and Movement Disorder Society (MDS) Task Force on Telemedicine in the Appendix, telemedicine programs for PD of various stages of maturity are operating globally and focus on both care and educational activities.…”
Section: Present: Increasing Access To Carementioning
confidence: 99%
“…32,44 Telestroke is now considered to be in the mainstream of clinical practice in the academic and community environments. 16,40 Furthermore, it has been demonstrated that high-quality telestroke consultations can be performed with mobile computers 3 and smartphones, 1,9,18 enhancing the portability of the service. There remain only two published randomized controlled trials of telestroke versus telephone methods of consultation for consideration of thrombolysis of acute ischemic stroke as of late 2013.…”
Section: Acute Ischemic Strokementioning
confidence: 99%
“…26 Since then, the practice of telestroke has been found to have a high interrater agreement with a bedside assessment of the National Institutes of Health Stroke Scale (NIHSS) score, 9,39,45 to enhance correct rt-PA decision making as compared with telephone-only consultation, 6,8,29 and to be cost-effective. 32,44 In light of these findings and the perception of benefit by acute stroke providers and patients, there has been growing interest in and a rapid expansion of telestroke networks both in the US 16,40 and internationally. 7 There has been less material published on and seemingly less use of telestroke infrastructure for the complex, multifaceted, and similarly important subacute phase of stroke evaluation and management.…”
mentioning
confidence: 99%
“…Also, addressing reimbursement issues may facilitate broader application 55. Currently, 48 states in the USA and the District of Columbia provide some form of Medicaid reimbursement for telehealth services and 32 states in the USA and the District of Columbia have some kind of private payer policy for telehealth.…”
Section: Global Health Problem Analysismentioning
confidence: 99%